The Development of Externalizing Symptoms from Late Childhood through Adolescence: A Longitudinal Study of Mexican-Origin Youth - Atherton, Olivia E. (Dev Psychol, 2017)
Youth who exhibit externalizing problems during childhood and adolescence are at an increased risk for a wide range of detrimental life outcomes. Despite the profound consequences of externalizing problems for children, their families, and their communities, we know less about the precise trajectory of externalizing symptoms across late childhood and adolescence, due to the paucity of fine-grained longitudinal research. The present study examined the development of externalizing symptoms in a large sample (N=674) of Mexican-origin youth, assessed annually from age 10 to 17. Specifically, we conducted analyses to better understand the trajectories of Attention-Deficit/Hyperactivity Disorder (ADHD), Oppositional Defiant Disorder (ODD), and Conduct Disorder (CD) symptoms (and their co-development), as well as how gender and cultural factors influence symptom trajectories. On average, ADHD symptoms slowly declined from age 10 to 17; ODD symptoms increased until age 13 and then declined thereafter; and, CD symptoms slowly increased until age 15 and then leveled off. ADHD, ODD, and CD symptoms predicted change in each other, indicating youth may accumulate multiple forms of externalizing problems over time. Boys reported fewer externalizing problems than girls, contrary to expectations. Consistent with the Immigrant Paradox, we found that 2(nd)+ generation youth, youth who endorsed fewer traditional Mexican cultural values (traditional gender roles, traditional family values, religiosity), and youth who engaged in less Spanish/more English language use were at increased risk for exhibiting ADHD, ODD, and CD symptoms from childhood through adolescence. We discuss the theoretical and practical implications of these developmental patterns among Mexican-origin youth. (248/250 words)